“O ícone do Deus invisível” Cl 1,15: iconografia bizantina, sua gênese, teologia e redescoberta na igreja católica do Brasil - Soares, Denis Ricard de Souza (2019)
This dissertation presents a stud on the resumed of Byzantine Iconography in the Roman Catholic Church in a particular manner in Brazil as an answer to the search for a return to Christian liturgical sources proposed by the Second Vatican Council (1962-1965). To understand this phenomenon, we will know the genesis of this style of sacred art from the 4th Century, the theological conflicts that arose around the pictorial representation of God, its canonical deferment in Ecumenical Council in the 8th Century and the role of the iconographer, the writer icons, as minister of the Church through art. Because this artistic style is an expression of the Catholic faith, it will be known the scopes of theology that underlie that, the sacred as a manifestation of the absolute, and the bases that assure the continued sacramental presence of the one that in the icon is evoked. Philosophical scopes are also contemplated, and sacred geometric symbols and colors too. After knowing the elements and the history of this artistic style, it will be possible to analyze the arrival of this art in contemporary Catholic Christian liturgical spaces, taking into consideration that these, like the faithful, are marked by a devotional baroque culture. Some artistic works are also presented that represent some Brazilian iconographers in the most diverse regions of the country. It was used the following methodology: the bibliographic method with a qualitative approach, field research and interviews with iconographers and liturgists. The principal goal of this research is to investigate the strong return of the Byzantine icons, art of the first Christian millennium, in current contemporary sacred pictorial productions of Brazil, either in a stylized way or in the traditional technique. In the context of the history of Eastern and Western culture, in their liturgical-doctrinal communication, concepts on liturgical liturgical art are presented through reflections of some authors such as Donadeo (1996), Evdokimov (1990), Gharib (1997), Pastro (2010), Floriênski (2012), Mondzain (2013), Tommaso (2017), among others